Symbolism, Space, and Social Connectedness in the Nggowo Lemah Tradition: Revisiting the Logic of Local Culture - Fajrul Falah Al-Azhari; Wahidah Zein Br Siregar (Serambi Madina: Journal of Islamic Studies, 2026)
This study aims to examine the cultural meaning, psychological function, and dynamics of the transformation of the nggowo lemah tradition in the context of house moving among Javanese communities in three villages: Calungan, Beru, and Candisari. This study uses a qualitative approach with in-depth interviews, direct observation, and interpretive analysis of the informants' lived experiences. The research findings indicate that nggowo lemah is practiced as a simple and adaptive domestic custom that focuses on the symbolic act of carrying a handful of soil from the old house to the new one. This tradition has a strong emotional function, especially in building a sense of security, spatial continuity, and attachment to the original environment, without being related to religious legitimacy. The results also reveal a generational shift, where younger groups tend to abandon this practice due to a more practical orientation to life, so that its sustainability is highly dependent on social and emotional relevance in the context of modern society. Overall, this study confirms that nggowo lemah is a cultural practice that functions as a psychosocial transition mechanism in the process of adaptation to a new space.